The equation of this graph is y = 2/3x − 4


What transformation would need to happen for the equation of the line to be y = 2/3x
?

(1 point)

1 answer

To transform the equation \( y = \frac{2}{3}x - 4 \) to \( y = \frac{2}{3}x \), you need to eliminate the constant term in the first equation.

In this case, the transformation required is to shift the graph upwards by 4 units. This means that you would be adding 4 to the entire function:

\[ y = \frac{2}{3}x - 4 + 4 = \frac{2}{3}x \]

So, the transformation needed is an upward shift of 4 units.